The Effect of Length of A3-51 Probiotic Supplementation to The Number of Intestine Enterobacteriaceae in Oreochromis niloticus - Dewi Desnilasari; Sukanto Sukanto; Agus Irianto (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
The aim of this research was to know the effect of length of A3-51 probiotic  supplementation  to the number   of   intestine   Enterobacteriaceae.   Research   used   experimental   method   using   Completely Randomized  Design  which  was  based  on  4   treatments  i.e.  La  (without  probiotic),  Ll  (probiotic supplementation for 7 days), L2 (probiotic supplementation for 14 days), L3 (probiotic supplementation for 21 days). Each  treatment was repeated 3 times. The result showed that the length period of A3-51 probiotic   supplementation  very   significantly  (P<0,01)  increased  the  intestine   Enterobacteriaceae number. However, in the same time the amount of pathogenic Enterobacteriaceae decreased. In addition, probiotic supplementation improved protein, fat, and carbohydrate digestions.   Key words: Enterobacteriaceae, intestine, probiotic, nutrient digestibility